Coping in Newly Diagnosed, Spanish-Speaking Men who Have Sex with Men and Live with HIV: A Bayesian Approach - Garrido-Hernansaiz, Helena; Alonso-Tapia, Jesús; Martín-Fernández, Manuel (European Journal of Mental Health, 2019)
The use of coping strategies depends on the type of adversity, and HIV infection creates different difficult situations to cope with. However, most coping questionnaires do not consider its situational character. This study sought to analyze coping and its effectiveness in the case of newly diagnosed HIV-positive Spanish-speaking men who have sex with men (MSM), for which a short form of the Situated Coping Questionnaire for Adults (SCQA) was validated in this population. 115 such diagnosed Spanish-speaking MSM (mostly from Spain and Latin America) completed the SCQA along with anxiety, depression, health-related resilience, and disclosure measures. Four models were compared through Bayesian structural equation modeling to test factorial validity; reliability coefficients were obtained, and criterion validity was ascertained via correlation analyses. The model considering the type of situation was superior to the rest, reliability was adequate, and coping strategies were shown to be related to anxiety, depression, resilience, and degree of disclosure. The short form of the SCQA is a valid means of assessing situated coping among Spanish-speaking HIV-positive MSM and, when used with other measurement tools, can be informative about coping effectiveness.